Keterbukaan Keuangan Partai Politik Terhadap Praktik Pencucian Uang Dari Hasil Tindak Pidana Korupsi - Laurensius Arliman S (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2016)
Abstract: Elections means implementation of the sovereignty of the people held in directly, general, free, confidential, honest, and fair in the Republic of Indonesia under Pancasila and the Constitution of the Republic of Indonesia Year 1945. The implementation of the election has a lot of dynamics, among others political boat fees are expensive, expensive campaign funds to political imagery, the cost of consultations and surveys are expensive as well as winning money politics. Financial disclosure is very important political party in an election, because a lot of the flow of the corruption that is used in the election. As a result, people do not believe in political parties, or some communities in Indonesia began to no longer sympathetic to the political party. The idea of political party financial disclosure regulations should be initiated carefully in Indonesian election codification plan. Forward Indonesia must have arrangements campaign funds or political funds transparent, accountable, and has strict sanctions and binding on the parties involved, so that people come back believing again to political parties, and assured political parties place to channel their aspirations in granting the right in elections Abtrak: Pemilu adalah sarana pelaksanaan kedaulatan rakyat yang diselenggarakan secara lansung, umum, bebas, rahasia, jujur, dan adil didalam Negara Kesatuan Republik Indonesia berdasarkan Pancasila dan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Pelaksanaan pemilu memiliki banyak dinamika, antara lain biaya perahu politik yang mahal, dana kampanye yang mahal untuk politik pencitraan, ongkos konsultasi dan survei pemenangan yang mahal serta politik uang. Keterbukaan keuangan partai politik sangat penting didalam pelaksanaan pemilu, karena banyak aliran hasil korupsi yang dipakai dalam pemilu. Akibatnya masyarakat tidak percaya kepada partai politik, atau sebagaian masyarakat Indonesia mulai tidak lagi simpatik pada partai poltik. Gagasan regulasi keterbukaan keuangan partai politik harus digagas dengan seksama didalam rencana kodifikasi pemilu Indonesia. Kedepan Indonesia harus memiliki pengaturan dana kampanye atau dana politik yang transparan, akuntabel, serta memiliki sanksi yang tegas dan mengikat para pihak yang terlibat, sehingga masyarakat kembali percaya lagi kepada partai politik, dan yakin partai politik tempat menyalurkan aspirasi mereka dalam pemberian hak dalam pemilu. DOI: 10.15408/jch.v4i2.3433